Diseño y construcción de un taladro de pedestal acoplado a personas zurdas, para la perforación en placa de acero A-36 hasta 20 mm de espesor y 18 mm de diámetro considerando el análisis ergonómico - Duque Pachay, Galo Rodrigo (2017)
This project will be emphasized in the small metal-mechanical industries, especially the left-handed people who perform the drilling process. The design of the pedestal drill coupled to left-handed people will focus on the improvement and optimization of times in repetitive production, where their performance and use of the aforementioned operators can perform the drilling process without work accidents. Chapter one, covers all information about left-handed people at the time of drilling, which is physical and static ergonomics, postures and inclinations. Chapter two, deals with the most appropriate calculations with which the drilling of pedestal for left-handers will be made, starting from the cutting speed until the calculation of the force of the pedestal axis. Chapter three, performed a series of statistical tests on sinister people in the process of drilling to verify the ability, ergonomics, effort and regularity, at the time of the drilling operation, so that the effectiveness of times and movements could be evidenced. Chapter four, is based on the analysis and materials costs with which will be built the drilling of pedestal.